Progress and Future Challenges of Human Induced Pluripotents Stem Cell in Regenerative Medicine - Anna Meiliana; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2011)
BACKGROUND: Less than a decade ago the prospect for reprogramming the human somatic cell looked bleak at best. It seemed that the only methods at our disposal for the generation of human isogenic pluripotent cells would have to involve somatic cell nuclear transfer (SCNT). Shinya Yamanaka in August 2006 in his publication (Cell) promised to change everything by showing that it was apparently very simple to revert the phenotype of a differentiated cell to a pluripotent one by overexpressing four transcription factors in murine fibroblasts.CONTENT: Mouse and human somatic cells can be genetically reprogrammed into induced pluripotent stem cells (iPSCs) by the expression of a defined set of factors (Oct4, Sox2, c-Myc, and Klf4, as well as Nanog and LIN28). iPSCs could be generated from mouse and human fibroblasts as well as from mouse liver, stomach, pancreatic, neural stem cells, and keratinocytes. Similarity of iPSCs and embryonic stem cells (ESCs) has been demonstrated in their morphology, global expression profiles, epigenetic status, as well as in vitro and in vivo differentiation potential for both mouse and human cells. Many techniques for human iPSCs (hiPSCs) derivation have been developed in recent years, utilizing different starting cell types, vector delivery systems, and culture conditions. A refined or perfected combination of these techniques might prove to be the key to generating clinically applicable hiPSCs.SUMMARY: iPSCs are a revolutionary tool for generating in vitro models of human diseases and may help us to understand the molecular basis of epigenetic reprogramming. Progress of the last four years has been truly amazing, almost verging on science fiction, but if we can learn to produce such cells cheaply and easily, and control their differentiation, our efforts to understand and fight disease will become more accessible, controllable and tailored. Ability to safely and efficiently derive hiPSCs may be of decisive importance to the future of regenerative medicine.KEYWORDS: iPSCs, ESC, reprogramming factor, reprogramming efficiency, somatic cell